2020
DOI: 10.1039/d0ce00546k
|View full text |Cite
|
Sign up to set email alerts
|

Facile and selective synthesis of zeolites L and W from a single-source heptanuclear aluminosilicate precursor

Abstract: Zeolites are usually synthesized by hydrothermal reactions using monomeric or polymeric Al- and Si-containing precursors, whereas simple and direct routes for the rational synthesis of zeolites remain elusive. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Megakalsilite was first discovered in 2002, and only very few reports describe its synthesis. Recently, it was also obtained using a very specific aluminosilicate source, a single molecular precursor (PyH)­[Al­{Ph 2 Si­(OSiPh 2 O) 2 } 2 ] (PyH = pyridinium cation) . Megakalsilite and related potassium feldspars are precursor phases for leucite production, which find applications in ceramics and porcelain-fused-to-metal systems …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Megakalsilite was first discovered in 2002, and only very few reports describe its synthesis. Recently, it was also obtained using a very specific aluminosilicate source, a single molecular precursor (PyH)­[Al­{Ph 2 Si­(OSiPh 2 O) 2 } 2 ] (PyH = pyridinium cation) . Megakalsilite and related potassium feldspars are precursor phases for leucite production, which find applications in ceramics and porcelain-fused-to-metal systems …”
Section: Resultsmentioning
confidence: 99%
“…32 With increasing water content, the K + signal narrows from 170 to 30 Hz and shifts downfield from 3.7 to 0.0 ppm. Increasing the availability of water increases the average coordination number of oxygen atoms from water, thus modifying the cation environment, as indicated by the change in 39 K chemical shift toward a more shielded environment. The associated weakening of the ionpairing strength simultaneously can be expected to enhance the kinetics of chemical exchange between potassium in different local environments, similar to what has been reported in literature for Na.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MPs with Si–CR-type leaving groups have been considered as a potential alternative to those with Si–OR-type leaving groups for the construction of aluminosilicates. Si–C bonds are easy to handle and can be activated, they are thermally more active than Si–O bonds, and numerous compounds with Si–C bonds have already been reported. , Among the MPs with Si–CR-type leaving groups, we focused on those with Si–Ph bonds, for which a variety of secondary building unit (SBU)-like MPs have been reported. We have previously demonstrated that a molecule that consists of a tetrahedral Al and six Si atoms with a spiro-7 core supported by 12 Si–Ph bonds, (PyH + )­[Al­{Ph 2 Si­(OSiPh 2 O) 2 } 2 ] − ( PyH + [AlSi 6 ] − ; PyH + = pyridinium cation; Figure ), can be transformed into two zeolites (zeolites L and W) in the presence of KOH under hydrothermal conditions accompanied by base-assisted Si–Ph bond activation . It should be emphasized here that the use of PyH + [AlSi 6 ] − has advantages over synthetic routes that use conventional separate precursors in terms of reproducibility, selectivity, and crystallinity of the two zeolites. On the other hand, the studies also demonstrated that the resulting zeolites L and W possess Si/Al ratios of 1.0–1.2, which are lower than that of PyH + [AlSi 6 ] − ( i .…”
Section: Introductionmentioning
confidence: 99%